The Coming Race War : And Other Apocalyptic Tales of America after Affirmative Action and Welfare. - Delgado, Richard (NYU Press, 1996)
In The Washington Post, Julius Lester praised Richard Delgado's The Rodrigo Chronicles: Conversations about America and Race as free of cant and ideology. ... an excellent starting place for the national discussion about race we so desperately need. The New York Times has hailed Delgado as a pioneer in the study of race and law, and the Los Angeles Times has compared his storytelling style to Plato's Dialogues. In The Coming Race War?, Delgado turns his attention to the American racial landscape in the wake of the mid-term elections in 1994. Our political and racial topography has been rad.